2019
DOI: 10.3390/plants8100369
|View full text |Cite
|
Sign up to set email alerts
|

Superhost Plants Alter the Structure of Plant–Galling Insect Networks in Neotropical Savannas

Abstract: Host plants may harbor a variable number of galling insect species, with some species being able to harbor a high diversity of these insects, being therefore called superhost plants. In the present study, we tested the hypothesis that the occurrence of superhost plant species of genus Qualea (Vochysiaceae) affects the structure of plant–galling insect ecological networks in Brazilian Cerrado. We sampled a total of 1882 plants grouped in 131 species and 43 families, of which 64 species and 31 families of host p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In the case of highly specialized plant‐galling networks, as gall‐inducers tend to be species‐specific, the occurrence of super host plants can be the main driver of the network structure (Araújo et al . 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of highly specialized plant‐galling networks, as gall‐inducers tend to be species‐specific, the occurrence of super host plants can be the main driver of the network structure (Araújo et al . 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…For the tropical region, Araújo et al . (2019b) described several plant‐galling networks in Neotropical savannas, which presented low values of connectivity but varied depending on the occurrence of super‐host plants.…”
Section: Introductionmentioning
confidence: 99%
“…Edge habitats may affect herbivore abundance in different ways; first, through a negative influence of microclimatic conditions on species fitness, although this effect may be ameliorated for leaf miners given the internal development of their larvae (Hespenheide, 1991); second, forest edges reduced plant diversity which, in turn, had a positive effect on herbivores abundance, possibly though a benefit from mixing their diet (Schuldt et al, 2010;Strong et al, 1984); third, a dilution of resources for herbivores, as predicted by the resource concentration hypothesis (Root, 1973), may result as a consequence of mixing ruderal and forest specialist plants occurring at forest-crop transitions (de Casenave et al, 1995;Erdős et al, 2019). Although we did not include plant species composition in our analysis, a previous study reported changes in plant assemblages at forest edges in the study area (Cagnolo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Graphic examples of the three hypotheses proposed for chain length changes in plant‐herbivore‐parasitoid food webs in fragmented habitats (upper half of the panels), and meta‐models depicting the hypothesized direct and indirect effects of habitat area and interior/edge position on chain length ( cl ) changes (bottom half of the panels). Arrows in black represent direct effects of variables according to three mechanisms: (a) Pyramid hypothesis: we expect larger areas and interior position to allow higher population densities (Connor et al, 2000), which cascades into higher number of consumers (Liu et al, 2017; Stevens & Carson, 1999), increasing cl ; (b) trophic rank hypothesis: the area reduction and edge position have a pronounced effect on species richness and population densities at higher trophic levels (Pinho et al, 2017), shortening cl ; and (c) connectivity hypothesis: the positive relation between habitat area and interior position on species richness increases the chance of including species with particular connectivity patterns (de Araújo et al, 2019; Dyer, 1995; Mulatu et al, 2004; Singer et al, 2019). Changes in species connectivity patterns will be reflected by the number of consumers ( V ) and/or resources ( G ) per species, and consequently affect the number of paths and the amount of biomass reaching the top trophic level.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Guapira opposita is cited as super host species in almost all inventories at restinga (review in Maia, 2013), except in Grumari and Guarapari. Recent evidence suggests that the presence of super host taxa can modify the structure of plant-galling networks in Neotropical environments, increasing the diversity and connectivity of interactions (Araújo et al, 2019c). In addition, the presence of super host species can impact the robustness of the network, because although it increases the robustness for random extinctions, the presence of closely connected species makes the network more vulnerable to directional attack (Iyer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%